Effect of boron on microstructure evolution and properties of wear-resistant cast Fe–Si–Mn–Cr–B alloy - Zhang Changle; Li Shouhai; Lin Yinghua; Ju Jiang; Fu Hanguang (Journal of Materials Research and Technology, 2020)
The purpose of this study was to clarify the effect of boron content on the microstructure evolution, mechanical properties, and three-body abrasive wear property of as-cast Fe–Si–Mn–Cr–B alloys, and to reveal the wear mechanism of Fe–Si–Mn–Cr–B alloys. The results indicated that the microstructure of the Fe–Si–Mn–Cr–B alloy was mainly composed of bainite, retained austenite (RA), M3B2, and M2B (M stands for the metal atom, in this case, it refers to Fe, Cr, and Mn). With the increase of boron content, the volume fraction of the boride phase increased, the morphology of the boride phase was dominated by fishbone, the microhardness of the boride phase and the macrohardness of the alloy increased, and the wear resistance of the alloy was significantly enhanced. Compared with the 0.5 wt.% B alloy, the macrohardness of the 2.0 wt.% B alloy was increased by 19.5%, the maximum microhardness of the boride phase reached 1440 HV0.2, the Charpy impact toughness was reduced by 45%, and the wear resistance was increased by 268%. The morphology, content and distribution of the boride phase play a key role in improving the hardness and wear resistance of the alloy. The synergy between the high-hardness boride phase and the softer metal matrix phase, which was composed of bainite and RA, gave the alloy excellent wear resistance. The main wear mechanisms of the alloy were abrasive wear and fretting wear.